Jalan Panjang Hubungan Antaragama di Indonesia - Taqiyudin Zarkasi (Al-Riwayah : Jurnal Kependidikan, 2017)
The struggle for independence was perceived by Muslims as a struggle for liberation not only the nation from colonialism, but also to liberate them from the religion of oppressors who come from other religions. These sentiments gained strong momentum when put in a historical context of the time, especially the harsh reality that the civilization of the Islamic world, which in the past grew rapidly and peaked brilliant, when it was sunk so deep, fell under Western colonialism that in fact claimed to Christian civilization. Of course, dissect interfaith relations in Indonesia must necessarily look at the history in which religions act in the constellation of politics since the country’s standing, even since before independent. Naturally, unpack these issues cannot be separated from the relation between religion and state as two of the most powerful institutions in the stage of world history. Patron-client relationship that is very hierarchical social character that forms as a religious group that is subordinate to the colonial powers, both in the religious and political dimensions. Compliance as servant relations among Christian missionaries in the future will be more colorful. Such circumstances make it difficult for the Christians when they are faced with a political choice for independence from the Dutch colonizers